ANALISIS KRITIS NEW HISTORICISM TERHADAP NOVEL INDONESIA MODERN DALAM KERANGKA SEJARAH SASTRA - Sugiarti Sugiarti (LITERA, 2009)
This study is aimed at (1) describing issues in three novels based on NewHistoricism in Indonesian literature; (2) exploring the New Historicism Approach which can provide solutions to possible changes in socio-cultural aspects and publishing industry; (3) finding new fundamental concepts which can contribute to the development of Indonesian literature. For this purpose, the study employed the qualitative phenomenological approach with the qualitative content analysis. The data were in the form of sentence fragments relevant to the research focus. Besides, the data were supported by relevant information beyond the text contributing tothe existing text. From the analysis, it can be concluded that: (1) the issues that can be revealed based on New Historicism in the three novels are sexuality problems, freedom, sexual deviation, patriarchy, deconstruction and rejection, spiritual aspect, humanity, and creativity in entrepreneurship; (2) the New Historicism Approach uses harsh words, fantasy, language style modification, scientific exploration,philosophy, health problem, and spiritual experience to show something different; (3) concepts that contribute to the history of Indonesian literature are that texts constitute a contestation between some ideologies and social forces in unlimited place and time. Aesthetic issues female writers offer are not only as a new way of expression or another alternative but also show a high motivation to offer differentimages.